FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN NASABAH DALAM PENGGUNAAN BSI MOBILE: STUDI KASUS PADA BSI KC PALEMBANG SUDIRMAN - Dian Ariska Putri; Citra Pertiwi; Dian Horid (CV. Cendikiawan Muda Sriwijaya, 2025)
Technological developments drive innovation in the banking sector, one of which is through digitalization of services such as BSI Mobile. This study aims to determine the effect of service quality variables, ease of use, and risk perception on customer satisfaction at Bank Syariah Indonesia KC Palembang Sudirman. The approach used is a quantitative method of data processing using statistical analysis IBM SPSS 23. Primary data was obtained by distributing questionnaires to 100 respondents, namely customers who use the BSI Mobile application at Bank Syariah Indonesia KC Palembang Sudirman. In the data analysis technique, validity and reliability tests, classical assumption tests, multiple linear regression analysis were carried out, while hypothesis testing used the t test, f test and R2.The results of this study indicate that the variables of service quality and ease of use have a positive and significant effect on customer satisfaction in the BSI Mobile service of Palembang Sudirman Branch, the risk perception variable has no effect on customer satisfaction in the BSI Mobile service of Palembang Sudirman Branch. While simultaneously the three variables of service quality, ease of use and risk perception together have an effect on customer satisfaction of BSI Mobile users at Bank Syariah Indonesia KC Palembang Sudirman.